2022
DOI: 10.3389/fpubh.2022.836688
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID-19 Pandemic, Self-Esteem and Its Effect on Depression Among University Students in Saudi Arabia

Abstract: Background and AimsUniversity students are commonly identified as susceptible, suffering from higher anxiety, stress, and depression than the overall population. During the Corona Virus Disease pandemic (COVID), education was shifted to the virtual learning environment. Students' ambiguity regarding academic accomplishment, imminent careers, changes in social life, and other concerns all these factors played a role in amplifying their stress levels, anxiety, and depression worldwide. This study investigates un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
13
1
1
Order By: Relevance
“…Furthermore, Khoshaim et al [ 22 ] reported that about 35% of students experienced moderate to extreme anxiety levels. Azmi et al [ 23 ] observed that 75% of students suffered from various levels of depression, while 41% suffered from low levels of self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Khoshaim et al [ 22 ] reported that about 35% of students experienced moderate to extreme anxiety levels. Azmi et al [ 23 ] observed that 75% of students suffered from various levels of depression, while 41% suffered from low levels of self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted at different universities in Saudi Arabia, healthcare students had alarmingly high levels of depression [ 15 ], while students from Italy were also found to present depressive symptoms [ 13 ]. In a similar study conducted more recently, again in students from universities in Saudi Arabia, 75% of the students experienced some level of depression after being taught online for over a year [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the evidence suggests that it may decrease one’s academic performance [ 24 ], although many argue that it may support academic performance [ 25 ]. A study conducted in Saudi Arabia showed that over 40% of university students experience low self-esteem [ 16 ]. Another study reported that online learning posed some behavioral challenges for them [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Hasil yang didapat pada penelitian ini yaitu lebih banyak mahasiswa dengan rasa percaya diri yang rendah dapat disebabkan karena pada masa pandemi, seluruh kegiatan pembelajaran dialihkan menjadi pembelajaran secara virtual dimana hal ini dapat menjadi suatu kekhawatiran bagi mahasiswa mengenai prestasi akademik, karir yang akan datang, dan perubahan dalam kehidupan sosial. Menurut penelitian yang dilakukan Azmi et al (2022) 17 telah dibuktikan bahwa terdapat penurunan rasa kepercayaan diri pada mahasiswa selama pandemi.…”
Section: Metodeunclassified